(untitled) (Research, Society and Development, 2020)
Theorizing about the “soil” theme transmutes from the perspective of each individual and the use that is made of it. The approach to environmental education started in the middle of the 20th century, precisely in the 1990s, related to the awakening of the rational use of the soil with its management and conservation. In Brazil, the “Education in soils” projects started in the 19th century, with the same objective. The National Curriculum Parameters (PCNs) bring the solo theme inserted in elementary and high school, both in the disciplines of Science, Geography, and Biology. We tried to verify what elementary and high school students from public and private schools know about soil in schools in Ceará, more precisely in Maciço de Baturité. The application of questionnaires in the cities of Pacoti, Redenção, Baturité based in Ceará and with a sample of 60 students in all, served as the basis for the study. We realize that students’ knowledge does not differ much from popular empirical knowledge about soil, even though they have learned about the topic at school, even if only a little. In this sense, we emphasize the importance of Education in Soils so that it is not only seen for economic purposes, in terms of fertility and management, but also as an element of the environment and the maintenance of life.